2019
DOI: 10.1002/mp.13726
|View full text |Cite
|
Sign up to set email alerts
|

Automatic large quantity landmark pairs detection in 4DCT lung images

Abstract: Purpose To automatically and precisely detect a large quantity of landmark pairs between two lung computed tomography (CT) images to support evaluation of deformable image registration (DIR). We expect that the generated landmark pairs will significantly augment the current lung CT benchmark datasets in both quantity and positional accuracy. Methods A large number of landmark pairs were detected within the lung between the end‐exhalation (EE) and end‐inhalation (EI) phases of the lung four‐dimensional computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 58 publications
(95 reference statements)
0
24
0
Order By: Relevance
“…ROI Dimension Modality End point [112] HN 3D CT TRE prediction [34] Lung 3D CT Registration error [31] Brain 3D MRI DSC score [47] Lung 3D CT Landmark Pairs [49] Lung 3D CT Registration error [138] Lung 3D CT Registration error…”
Section: Referencesmentioning
confidence: 99%
“…ROI Dimension Modality End point [112] HN 3D CT TRE prediction [34] Lung 3D CT Registration error [31] Brain 3D MRI DSC score [47] Lung 3D CT Landmark Pairs [49] Lung 3D CT Registration error [138] Lung 3D CT Registration error…”
Section: Referencesmentioning
confidence: 99%
“…One of the advantages of Siamese networks is that they can facilitate one-shot learning which requires minimal training data. This application is similar to the study presented by Fu et al who suggested a Siamese network architecture for automatic landmark pair detection in 4DCT lung images [20]. However, while their approach is dependent on a large dataset of manually, annotated images, we make use of data augmentation and simulation instead.…”
Section: Networkmentioning
confidence: 78%
“…Traditional approaches to calculating these metrics face the same challenges as manual registration (exhaustive operator intervention, time intensive, high cost, etc.). Because of this, DL methods have also been proposed for performing these evaluations [20][21][22][23]. However, DL-based evaluation strategies are all supervised and heavily reliant on access to large manually annotated datasets which makes it difficult to apply them to emerging imaging techniques [24].…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning-based DIR methods have been proposed for MRI brain, 21 CT head/neck, 22 CT chest, 23 MR/US prostate, 24 4D-CT lung [25][26][27][28] and so on. 29 Eppenhof et al proposed a supervised convolutional neural network (CNN) using U-Net architecture.…”
Section: Related Workmentioning
confidence: 99%
“…Deep learning‐based DIR methods have been proposed for MRI brain, CT head/neck, CT chest, MR/US prostate, 4D‐CT lung and so on . Eppenhof et al .…”
Section: Related Workmentioning
confidence: 99%